Application of Tilapia Skin Acellular Dermal Matrix to Induce Acute Skin Wound Repair in Rats - Lv, Kangning; Wang, Lei; He, Xiaoli; Li, Wenjun; Han, Lei; Qin, Song (Frontiers in Bioengineering and Biotechnology, 2022)
Extracellular matrix (ECM) material with good biological activity is essential to simulate cell growth microenvironment, induce cell infiltration and angiogenesis, and promote the repair of large area acute skin wound. In this study, tilapia skin acellular dermal matrix (TADM) was prepared to simulate ECM microenvironment, which can promote substantial area acute wound healing in rats. The main component of TADM is type I collagen, which has good physical and chemical properties, biological activity and cell adhesion. TADM is a form of biomaterial with low immunogenicity, low risk of prion infection and lower economic cost than other related materials such as mammalian collagen biomaterials. Our results show that TADM can guide cell infiltration, angiogenesis, regulate the expression and secretion of inflammatory and skin repair correlated factors to promote tissue healing.